Optimization of Material Layout at the Warehouse Laboratory of PEM Akamigas through a Class Based Storage Approach - Pratama, Rendy Bagus; Putri, Citra Berliana (International Journal of Science and Society, 2025)
The PEM Akamigas Warehouse Laboratory serves as a vocational learning facility in oil and gas logistics, providing practical experience for students. However, the current warehouse layout is inefficient due to unstructured material placement and suboptimal movement flows. This research aims to redesign the warehouse layout using the Class based storage (CBS) approach, beginning with ABC-based classification of materials by movement frequency. Simulations were conducted using rectilinear distance analysis and evaluated across three storage modes: general storage, Dedicated Storage, and CBS. Results indicate that the proposed layout significantly reduces operational time, especially in CBS mode, which demonstrated uniform improvements in operator activity, run time, and transporter time. The CBS-based layout successfully streamlines material flow, optimizes warehouse space utilization, and enhances the realism of practical learning. Thus, the redesigned layout is not only more efficient but also supports educational objectives aligned with logistics industry standards.